2015
DOI: 10.1108/jcp-10-2014-0015
|View full text |Cite
|
Sign up to set email alerts
|

A predictive model of criminality in civil psychiatric populations

Abstract: Purpose -This study sought to develop a predictive model of criminal risk in civil psychiatric populations, by determining the relative impacts of 1) psychopathy, 2) drug use, 3) impulsivity and 4) intelligence on levels of criminality.Design/methodology/approach -The sample consisted of 871 civil psychiatric patients, selected from the MacArthur Violence Risk Assessment Study, who had been diagnosed with a mental illness or personality disorder, and hospitalised less than 21 days. Each participant was adminis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 56 publications
0
2
1
Order By: Relevance
“…With regard to impulsiveness, unlike previous findings [36,37], we found no differences between the two groups when rated by the BIS. Although there were differences in BGHA scores, the BDHI scores among cases were similar to those found in a study conducted among male prisoners [38].…”
Section: Discussioncontrasting
confidence: 99%
“…With regard to impulsiveness, unlike previous findings [36,37], we found no differences between the two groups when rated by the BIS. Although there were differences in BGHA scores, the BDHI scores among cases were similar to those found in a study conducted among male prisoners [38].…”
Section: Discussioncontrasting
confidence: 99%
“…Interestingly, it is no coincidence that studies have shown high correlation with drug use, intelligence, impulsivity, and psychopathy among those arrested in forensic and psychiatric populations. Evans et al note that drug use and impulsivity are highly indicative of criminal and psychotic behavior, meaning where drug use and psychological disorders meet, there will be crime [24].…”
Section: Complexities With Interventionmentioning
confidence: 99%
“…Aside from various drug debates, marijuana as the number one drug of abuse among this population raises the notion this is one finding that can help explain the difficulties in recognizing mental illness at its core. In other words, too often are there cases where someone suffering from a psychological disorder goes unnoticed until they reach a breaking point that leads to a criminal act; individuals who knew the person claim they had no idea about the illness [24]. It is plausible to think marijuana use has, for a period, masked the mental illness, allowing that person to appear normal until either increased use or cessation has induced a manic episode.…”
Section: Dickey Mrmentioning
confidence: 99%